Optical Mark Recognition Evaluation System using Dual-Component Approach - Dharmik, R. C.; Rangari, Sudhir; Jain, Sachin; Nilawar, Ajinkya; Deshmukh, Gopal; Yeole, Abhay (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The Optical Mark Recognition (OMR) Project represents a comprehensive effort to leverage advanced technology for automating the data capture and processing of paper based forms. In response to the increasing need for efficient and accurate data handling, this project introduces an OMR system designed to alleviate the challenges associated with manual data entry and processing. The core objectives include developing both hardware and software components capable of accurately interpreting user-marked responses on predefined areas of forms, such as surveys, exams, and questionnaires. The OMR system surpasses expectations in processing speed, boasting an average processing time of [insert time, e.g., seconds per sheet]. This efficiency positions the system as an ideal solution for high-throughput scenarios, including large-scale examinations or surveys. The project’s scope extends to various sectors, including education, healthcare, market research, and government, where large volumes of data must be collected and analyzed expeditiously. The significance of OMR technology lies in its ability to enhance speed, accuracy, and reliability in data processing. By automating traditionally labor-intensive tasks, the project aims to improve overall productivity, reduce costs, and minimize errors inherent in manual data processing methods. .The methodology adopted for the OMR project involves the integration of optical scanners for physical data capture and sophisticated software algorithms for image processing, mark detection, and data extraction. This dual-component approach ensures a seamless and efficient OMR system capable of handling diverse forms.